Existence and uniqueness of maximal strong solution of a 1D blood flow in a network of vessels. (February 2022) - Maity, Debayan; Raymond, Jean-Pierre; Roy, Arnab
Abstract: We study the well-posedness of a system of one-dimensional partial differential equations modeling blood flows in a network of vessels with viscoelastic walls. We prove the existence and uniqueness of maximal strong solution for this type of hyperbolic/parabolic model. We also prove a stability estimate under suitable nonlinear Robin boundary conditions.